(untitled) (Proceeding of SINERGY, 2026)
This study aims to develop a web-based tourism information system for Kampoeng Lawas Maspati to improve digital information management and support sustainable community-based tourism. Field observations and stakeholder interviews identified challenges, including limited digital documentation, unstructured content, and difficulties in information dissemination. To address these issues, the Rapid Application Development (RAD) methodology was employed, consisting of requirements planning, RAD design workshop, and implementation phases. Collaborative engagement with community members ensured the system aligned with user needs and reflected local cultural identity. Functional requirements were translated into system models, including use case and activity diagrams, database design, and interface prototypes. The implementation phase involved coding and black-box testing to validate system functionality. Test results confirmed that all features operated according to specifications. The developed system delivers comprehensive information on village profiles, historical sites, tourism activities, facilities, and tour packages, while providing administrators with content management capabilities. This solution enhances accessibility, promotes independent digital management by local stakeholders, and strengthens the capacity of the community in sustainable tourism promotion.